β-cyclodextrin cross-linked metal organic frameworks as a new sensing candidate for donepezil hydrochloride potentiometric sensors - Rehab O. El-Attar; Reda M. Abdelhameed; Elmorsy Khaled (BMC Chemistry)
Abstract Screen-printing is a well-established promising technology for large scale production of planner disposable electrochemical sensors. The present study aims to fabricate a novel donepezil hydrochloride (DPH) screen-printed sensor integrated with the cross-linked β-cyclodextrin-functionalized aluminum metal organic framework-multiwall carbon nanotubes nanocomposites (β-CD/MOF/MWCNTs) as a novel sensing element. The fabricated disposable sensors exhibit theoretical Nernstian compliance value of 60.7 ± 1.5 mV decade−1 within a linear dynamic concentration range from 10–6 to 10–2 mol L−1 and limit of detection 7.0 × 10 −7 molL−1. The DPH disposable sensors show high potential stability with a prolonged operational lifetime and the fast response time of 6 s. The presented electrochemical sensors represent an efficient analytical tool for fast and sensitive assay of DPH residues in the marketed pharmaceutical tablets and biological samples with acceptable average recoveries under direct potentiometric measurements, flow injection analysis (FIA), and potentiometric titration. Moreover, the dissolution and degradation studies of DPH can be monitored by the presented disposable sensors.